PENGARUH LATIHAN HOME BASE TERHADAP KECEPATAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB RAJAWALI KUANSING - Antonius Aris Kristiawan; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem addressed in this study is the lack of dribbling skills in players, too slow in dribbling and very stiff legs, so in this study it was titled